2008
DOI: 10.1111/j.1365-2672.2008.03814.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and identification of lactic acid bacteria and yeasts from sourMifen, a traditional fermented rice noodle from China

Abstract: Aims:  Considering the effect of natural fermentation on the textural improvement of fermented rice noodles in China and South Asia, and given the lack of reports concerning microbial populations and structure in the fermentation process, this study aims to determine the number of viable micro‐organisms and identify the species isolated from the local factories, and to assess their potential use as a starter culture from their enzymatic profiles. Methods and Results:  Fourteen samples from three local factorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 30 publications
4
31
0
Order By: Relevance
“…In addition, during fermentation at Phase II, the anaerobic condition created in the pit may favor their growth. This result is in line with Lu et al, (2008), who reported there is a general agreement on the dominance and beneficial effects of LAB on the fermentation process of starchy food products. Several authors in similar fashion reported yeasts as commonly the predominant microorganisms next to lactic acid bacteria during cassava fermentation and other food products (Oyewole, 2001;Mugula et al, 2003;Assanvo et al, 2006;Oguntoyinbo, 2008;Lu et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, during fermentation at Phase II, the anaerobic condition created in the pit may favor their growth. This result is in line with Lu et al, (2008), who reported there is a general agreement on the dominance and beneficial effects of LAB on the fermentation process of starchy food products. Several authors in similar fashion reported yeasts as commonly the predominant microorganisms next to lactic acid bacteria during cassava fermentation and other food products (Oyewole, 2001;Mugula et al, 2003;Assanvo et al, 2006;Oguntoyinbo, 2008;Lu et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…This may also signifies the role of the lactic acid bacteria that are contained in the traditional starter culture. Similar results have also been reported for other fermented food products (Kimaryo et al, 2000;Chamunorwa et al, 2002;Mugula et al, 2003;Muyanja et al, 2003;Inayara et al, 2005;Kostinek et al, 2007;Lu et al, 2008). The reduction of moisture content along with fermentation time mainly attributed to the activities of fermenting microorganisms.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…According to Lu et al (2008), isolates with α-glucosidase and β-glucosidase activities indicate the ability to digest polysaccharides. These isolates include Pediococcus pentosaceus, L. lactics, L. fermentum, L. delbruckii.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the volatiles 2-methylpropanoic acid and 3-methylbutanoic acid appear to form during the fermentation process, as indicated by the fact that they were not found in broken rice samples, but developed after fermentation for 24 h and then significantly decreased during the sedimentation step. The dominant species identified in khanom jeen were similar to mifen, in which the primary stage of rice fermentation was dominated by LAB and yeast 12 . Hence, these volatiles may result from the metabolic activities of LAB and yeast.…”
Section: Influence Of Fermentation On Volatilesmentioning
confidence: 89%